Development Education: A Conceptual Framework for a Comprehensive Counselling and Guidance Program - Gazda, George M. (Canadian Journal of Counselling and Psychotherapy, 2012)
Developmental education is defined. Its philosophical foundations and a rationale for its adoption are presented. Thirteen "content" modules on which developmental education might focus are then outlined. In conclusion, the implications for teachers, counsellors, and counsellor educators are noted.